The Passive Association Factor in Determining Transfer Pricing for Intra-Group Service Transactions: A Case Study of the Tax Court Decision on the Appeal Filed by PT SCI - Krisna Herdiana; Zakky Ashidiqi (LP2M IAIN Palopo, 2026)
This study explores the role of the passive association factor in determining transfer pricing for intra-group service transactions, focusing on the Tax Court’s decision in the PT SCI case. The research aims to clarify how passive association is treated under Indonesian regulations and its implications for the application of the arm’s length principle. Employing a qualitative descriptive case study approach, data were collected through in-depth interviews with tax authorities, practitioners, and academics, as well as document analysis of relevant regulations and court decisions. The population includes stakeholders in transfer pricing regulation and enforcement, with purposive sampling used to select key informants. Data were analyzed using coding, memoing, and thematic analysis to identify patterns and draw conclusions. The results show that passive association is often not eligible for remuneration, yet the lack of clear regulatory guidance leads to inconsistent interpretations and legal uncertainty. The study concludes that clearer criteria and practical guidelines are needed to distinguish passive from active association, ensuring fairer transfer pricing practices and dispute resolution in Indonesia.